Understanding the motions of the cheetah tail using robotics - Patel, Amir (Department of Electrical Engineering, 2015)
The cheetah is capable of incredible feats of manoeuvrability. But, what is interesting about these manoeuvres is that they involve rapid swinging of the animal's lengthy tail. Despite this, very little is understood about the cheetah tail and its motion, with the common view being that it is "heavy" and possibly used as a "counter balance" or as a "rudder". In this dissertation, this subject is investigated by exploring the motions of the cheetah tail by means of mathematic al models, feedback control and novel robot platforms. Particularly, the motion in the roll axis is first investigated and it is determined that it assists stability of high speed turns. This is validated by modelling and experimental testing on a novel tailed robot, Dima I. Inspired by cheetah video observations, the tail motion in the pitch axis during rapid acceleration and braking manoeuvres is also investigated. Once again modelling and experimental testing on a tailed robot are performed and the tail is shown to stabilise rapid acceleration manoeuvres. Video observations also indicate the tail movement in the shape of a cone: a combination of pitching and yawing. Understanding this motion is done by setting up an optimization problem. Here, the optimal motion was found to be to a cone which results in a continuous torque on the body during a turn while galloping. A novel two degree of freedom tailed robot, Dima II, was then developed to experimentally validate the effect of this motion. Lastly, measurement of the cheetah tail inertia was performed during a routine necropsy where it was found to have lower inertia than assumed. However, the tail has thick, long fur that was tested in a wind tunnel. Here it was found that the furry tail is capable of producing significant drag forces without a weight penalty. Subsequently, mathematical models incorporating the aerodynamics of the tail were developed and these were used to demonstrate its effectiveness during manoeuvres.